Enhancing chemoradiation of colorectal cancer through targeted delivery of raltitrexed by hyaluronic acid coated nanoparticles. Issue 29 (15th July 2019) - Rosch, Justin G.; Landry, Madeleine R.; Thomas, Charles R.; Sun, Conroy
Abstract : The combination of radiation therapy and nanomedicine allows for improved treatment outcomes in a murine colorectal cancer model. Abstract : Combined modality therapy incorporating raltitrexed (RTX), a thymidylate synthase inhibitor, and radiation can lead to improved outcome for rectal cancer patients. To increase delivery and treatment efficacy, we formulated a hyaluronic acid (HA) coated nanoparticle encapsulating RTX (HARPs) through layer-by-layer assembly. These particles were determined to have a diameter of ∼115 nm, with a polydispersity index of 0.112 and a zeta potential of −22 mV. Cell uptake in CT26 cells determined through flow cytometry showed a ∼5-fold increase between untargeted and HA-coated particles. Through viability and DNA damage assays, we assessed the potency of the free RTX and HARPs, and found increased DNA damage in cells treated with the RTX-loaded nanoparticles administered concurrently with radiation. In vivo efficacy through tumor growth inhibition was investigated in a syngeneic murine colorectal cancer model. Nanoparticle treatment showed no acute toxicity in vivo, and all treatments showed survival benefits for their respective groups compared to controls. HARPs alone slowed tumor growth, although not significantly. Radiation alone and in combination with the HARPs showed significant growth delay. Notably, the combination treatment significantly hindered tumor progression relative to the HARPs highlighting the benefit of this multipronged treatment. These results provide a foundation for loading RTX in a nanoparticle formulation, and establish a combined radiation and drug dosing schedule to determine optimal tumor growth delay and subsequent treatment efficacy.